UNDERPASS DALAM MANAJEMEN PEMBERITAAN MEDIA: Studi Deskriptif Kualitatif Tentang Manajemen Pemberitaan Kasus Underpass Makamhaji, Sukoharjo di Media Cetak Harian Umum Solopos dan Media Online Solopos.com Periode 1 Januari- 5 Maret 2013 - Nurjanah, Siti; Perwita, Alvika Hening; B.W, Sri Herwindya (JURNAL KOMUNITAS, 2013)
Solopos is the most existing press media in solo. Established in solo September 19th 1997,in that year solo was a city that had a bad reputation among press communities.. Right now Solopos was expanding its business by creating new media,it was online version of Solopos, Solopos.com. achievement that had been achieved by Solopos.com in the last 6 months (Januari-Juni 2013) was getting the most visitors in solo regional,about 50.000-60000 visitors a day. All of Solopos and Solopos.com success because of supported by good news management. In order to see the differences of news management of Solopos and Solopos.com, researcher connected with reporting of underpass, planning, organizing, actuating and controlling. The study was conducted in order to determine which news management applied in managing the news of Underpass. This research was a qualitative descriptive study. Results from press media management research in news management of Underpass was done in four stages, planning, organizing, actuating and controlling. In Planning Solopos.com was in the same side with Solopos butit was well planned because there was a planning meetings or editorial meeting every day at 15.00, all things were discussed in the meeting, such as headline proposals, and the selection of what theme would be written. Meeting was attended by all mediacandidates. Organizing the management reports on print media and online media Solopos.com had been formed organizational structure withits positions and duties. Actuating in management reporting begun with the reporting process, reporting was done by the same reporter, because the online media of Solopos.com didn’t has it. This reporting was done by doing it right in the field, in Makamhaji Sukoharjo. The news came ober of the rules of journalism. Controlling in management report was done by editors that thethe task was overseeing directly in the field issues (editor Solopos), overseeing incoming and outgoing news and watching the news to be published (Solopos.com editor) as well as overseeing the content of the news reporter with editing directly.